Crystal engineering in functionalized materials: from fundamentals to applications - Shunje, Kelly Nzwanai (Kansas State University, 2023)
The carbamate-bearing molecules and their derivatives are versatile compounds for crystal engineering because they contain multiple acceptor and donor sites for directional intermolecular interactions. In order to better understand the structural landscape of the carbamate functionality, two thiazole-based carbamate families (each with five members), R((2-thiazoyl)carbamothioyl)carbamate (1) and R((2-thiazoyl-5-methyl)carbamothioyl)carbamate (R=methyl>hexyl) (2) were synthesized as described in Chapter 2. We examined (i) the effect of increasing chain length (R=methyl>hexyl), and (ii) the effect of adding a methyl substituent on the thiazole ring on molecular packing. For series 1 the targets interact via (carbamate)N-H---N(thiazole) forming infinite chains and molecules pack by aggregating into hydrophobic layers with alkyl chains facing each other and pi-stacked layers of the thiazole rings. Addition of a methyl substituent on the thiazole ring in series 2 resulted in similar H-bonding and packing pattern from methyl to isobutyl. However, for longer pentyl and hexyl chains, the N–H---S=C dimer formed but the packing has alternating stacks of alkyl chains facing each other and thiazole rings facing each other. In Chapter 3, the structural influence of hydrogen bonding on structure was explored using diethyl N,N′-[(1,4-phenylenedicarbamothioyl)bis(carbamate)] (14thiol) as a core because it possesses various hydrogen bond donor and acceptor sites. Co-crystallization experiments were conducted using pyridine-based co-formers and two polymorphs, one dioxane solvate, three co-crystals and one co-crystal solvate (THF) were obtained. Introduction of pyridine-based co-formers disrupted the robust homomeric N–H---S=C and N–H---O=C H-bonded dimers in 14thiol with the formation of heteromeric N-H---N bonded co-crystals. Hirshfeld surface analysis was conducted to give insights into the nature of interactions, and it revealed that the high acceptor ability in the co-formers led to the increase in H-bonding interactions (N-H---N) and a decrease in (O---H) contacts in 14thiol co-crystals. Molecular geometry analysis showed how the target was able to adopt several molecular conformations in order to accommodate various co-formers thus yielding multicomponent solid forms. In Chapter 4, we investigated how the presence of multiple intermolecular interaction sites influence the heteromeric supramolecular assembly of three R-N-[(3-pyridinylamino) thioxomethyl] carbamates (R= methyl, ethyl, and isobutyl) with fluoroiodobenzenes. Three targets were synthesized and crystallized resulting in three parent structures, five co-crystals and one co-crystal solvate. MEP surfaces were employed to rank the relative importance of the binding sites (Npyr > C=S > C=O) in order to predict the dominant interactions. The N-H---H hydrogen bond (parent synthon) was replaced by I---Npyr in 3/6 cases by I---C=S in 4/6 cases and by I---O=C in one case. Interestingly, in two cases, the I---C=S halogen bond coexisted with I---Npyr and I---O=C halogen bonds. Overall, the MEPs were fairly reliable for predicting co-crystallization outcomes. Halogen-bond donors co-formers proved to be structurally competitive for acceptor sites even in the presence of strong hydrogen-bond donors. To investigate structure-property relationships in carbamates, Chapter 5, the ability to control thermal expansion (TE) behavior in solid state materials was studied. We examined (i) the effect of intermolecular interactions and molecular packing, and (ii) the effect of varying molecular dimensions (di->tri->tetra) carbamate on TE. Five targets were designed and synthesized: three fluorinated dicarbamates with varying chain lengths, one tri-carbamate and one tetra-carbamate. A series of detailed SCXRD structural determinations at 20-K intervals (150-250) allowed us to analyze the thermal expansion at molecular level. All five targets showed TE and the lower dimensional dicarbamates exhibited the highest TE. The specific influence of intermolecular interactions was explored based on interaction energies (IEs) using energy framework analysis which confirmed that IEs were highest along the direction of the robust N-H---O=C interactions which subsequently restricted thermal expansion along those directions. Finally, in Chapter 6, specific applications of crystal engineering were explored using hydrogen-bonded organic frameworks (HOF) as molecular containers/hosts for volatile fragrance compounds (cinnamyl alcohol and α-terpineol). In the first case, the HOF successfully captured α-terpineol in its pores via physical encapsulation, as indicated by thermal gravimetric analysis. In the second case, the HOF also captured cinnamyl alcohol by way of H-bonding to the volatile guest compound. We demonstrated that this supramolecular framework, based on trimesic acid, is very suitable for capture and slow release of volatile compounds.
Keywords: Crystal engineering; Hydrogen bonding; Halogen bonding; Multicomponent crystals; Thermal expansion; Hydrogen-bonded organic frameworks; Volatiles